Augmented Reality for Identifying Maintainability Concerns during Design - Imad A. Khalek; Jad M. Chalhoub; Steven K. Ayer (Advances in Civil Engineering)
In a building context, decisions made early in the design phase can have a major impact on maintainability of the resulting facility. Effectively leveraging the knowledge of facility management teams in the design stage can lead to improved maintainability in the operation phase, but this feedback can be challenging to elicit during the design stage because facility management teams may not be formed by the time of design. This requires designers, who may not have facility management experience, to think like facility managers in order to consider the needs of the maintenance teams. This paper examines the extent to which different visualization media may be able to enable individuals without prior maintenance experience to identify maintainability concerns in a design model. Student participants, without prior maintenance experience, were randomly assigned to explore a design to assess maintainability concerns with either augmented reality (AR) or a traditional computer screen for viewing a Building Information Model (BIM). Their perceptions, behaviors, and statements were recorded and analyzed. Results indicate that BIM supports better identification of potentially problematic areas, but AR allows users to more consistently determine why an area is problematic. This suggests an opportunity to use a hybrid BIM/AR approach for identifying and resolving maintainability considerations during the design phase. The findings from this work provide evidence to illustrate how AR and BIM may enable individuals with limited experience to be able to effectively think like facility managers in order to make better maintainability decisions during design to lead to a better building during operation.